Decreased energy impact on Life Cycle Assessment (LCA) of ceramic tiles using nanoparticles (2024)
One of the main aspects of the ceramic tile industry is the intensive energy consumption required in its processes to manufacture different products. This high energy demand, coupled with the associated costs and CO2 emissions, poses significant challenges to the sustainability of the industry. The high consumption of electrical and thermal energy is associated with each of the manufacturing processes, driven by both electrical power and various fossil fuels in the form of hot gases. In recent years, there has been a growing interest in the ceramic tile industry in reducing energy intensity and material consumption, leading to the implementation of life cycle assessment (LCA) studies for ceramic tiles. The industry has explored alternatives such as the use of residual heat, renewable energies, and thickness reduction to improve energy efficiency. There is also a need to explore further alternatives, including the incorpora- tion of nanoparticles into ceramic materials, to reduce the life cycle impact of ceramic tile manufacturing. This study aims to explore the feasibility of using nanoparticles to reduce the life cycle impact of ceramic tiles. The LCA approach in this research explores various alternatives to mitigate environmental and economic impacts through the incorporation of nanoparticles. By adopting a “cradle to gate” approach and a systematic methodology, this study leverages technological innovation management to understand the system’s components and their interactions. The analysis includes strategies such as reducing the thickness of the tiles, thereby improving mechanical resistance, and increasing thermal conductivity. These enhancements are achieved through an innovative mixture of ceramic materials and nanoparticles, aimed at reducing the overall life cycle impact of ceramic tile production. The findings of this research indicate that incorporating nanoparticles can significantly reduce energy consumption during the tile manufacturing process and decrease GHG emissions. Additionally, improvements in the durability and strength of the tiles were observed, adding value to the final product. This thesis provides a detailed analysis of the environmental and economic impacts of these innovations, proposing a sustainable model for the ceramic industry in Colombia. The results underscore the potential for magnetite nanoparticles to contribute to a more sustainable ceramic tile industry, aligning with global efforts to mitigate climate change and promote environmental stewardship. The comprehensive analysis conducted in this thesis highlights the significant potential of inte- grating magnetite nanoparticles into the ceramic tile manufacturing process. This integration not only addresses critical environmental concerns but also enhances the product’s performance and market competitiveness. Through a detailed examination of the life cycle impacts and the development of innovative production techniques, this research offers valuable insights and practical solutions for advancing the sustainability of the ceramic tile industry in Latin America.